Attitudes and Perceived Barriers to Sexually Transmitted Infection Screening Among Graduate Medical Trainees. Issue 10 (October 2021) - Zucker, Jason; Carnevale, Caroline; Theodore, Deborah A.; Castor, Delivette; Meyers, Kathrine; Gold, Jeremy A. W.; Winetsky, Daniel; Scherer, Matt; Cohall, Alwyn; Gordon, Peter; Sobieszczyk, Magdalena E.; Olender, Susan
Abstract : Abstract: Graduate medical training is an opportune time to improve provider delivery of sexually transmitted infection (STI) screening. A survey of trainees found that the majority feel STI screening is their job but identified barriers to successful screening. Training that intentionally address service-specific barriers will be valuable in ending the STI epidemic. Abstract : A survey of graduate medical trainees found that the majority feel sexually transmitted infection screening is their job but identified barriers to successfully screening their patients